Local Economic Development Through Halal Tourism in Kambo Village (International Journal of Economics and Management Research, 2026)
This research is motivated by the great potential for halal tourism development in Kambo Village, Palopo City, which has a wealth of natural mountains, waterfalls, clean rivers, and community gardens as tourist attractions. However, this potential has not been optimally utilized due to minimal management, the lack of directed regulations, and the lack of integration of local wisdom with halal tourism standards. This condition raises questions about how this potential can be developed effectively in accordance with sharia principles and the needs of Muslim tourists . The research problem formulation includes: (1) how the halal tourism potential in Kambo Village is reviewed from the aspects of nature, culture, and community readiness, (2) what is the role of the community and MSMEs in the halal tourism ecosystem, and (3) what are the dynamics of collaborative governance and integrative models for local economic development based on halal tourism. The research uses a qualitative descriptive method with a case study approach and deductive analysis. Data were obtained through observation, interviews, and document reviews related to regional spatial planning. The results show that Kambo has strong potential as a halal tourism area, but its development has not been maximized due to limited infrastructure, the absence of halal certification or standards, and minimal government facilitation and promotion. By strengthening regulations, increasing community capacity, and developing sharia-compliant facilities and infrastructure, Kambo has the potential to develop as a leading halal tourism destination in Palopo City